2012
DOI: 10.1016/j.jjcc.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of isoproterenol and propranolol on the inducibility and frequency of ventricular fibrillation in patients with Brugada syndrome

Abstract: ISP suppressed induction of VF and the increase of DF with time. PRO aggravated VF and accelerated DF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
(44 reference statements)
1
16
0
Order By: Relevance
“…Further, a higher dominant frequency (DF) of the VF was noted in high‐risk patients with Brugada syndrome [44]. The pharmacological change in the DF during VF in patients with Brugada syndrome was consistent with findings indicated in previous reports [45]. These findings might indicate that investigating the characteristics involved in inducing VF may have potential as a predictive value for sudden cardiac death in asymptomatic Brugada syndrome.…”
Section: The Indications For Icd Placement For the Primary Preventionsupporting
confidence: 89%
“…Further, a higher dominant frequency (DF) of the VF was noted in high‐risk patients with Brugada syndrome [44]. The pharmacological change in the DF during VF in patients with Brugada syndrome was consistent with findings indicated in previous reports [45]. These findings might indicate that investigating the characteristics involved in inducing VF may have potential as a predictive value for sudden cardiac death in asymptomatic Brugada syndrome.…”
Section: The Indications For Icd Placement For the Primary Preventionsupporting
confidence: 89%
“…Third, we did not evaluate pathological myocardial damage by biopsy, structural changes by cardiac magnetic resonance imaging, or gene mutations [28]. The association between myocardial damage and b-adrenergic agonists was also not evaluated in the present study [29].…”
Section: Study Limitationsmentioning
confidence: 80%
“…Namely, in a 67-year-old woman with the Brugadatype ECG, ISP infusion reduced the ST-T elevation and unexpectedly demonstrated a lack of late r wave in lead V 1 . Subsequent reports, including the report by Omiya et al, confirmed a similar ECG-ST segment response to ISP infusion [1,4]. Also, association between the fluctuation of the ECG-ST level and the changes in r of QRS complex in the right precordial leads is described in patients with Brugada-type ECG [4].…”
mentioning
confidence: 77%
“…I read with interest the report by Omiya et al on the effects of isoproterenol (ISP) and propranolol on the inducibility of malignant arrhythmia in patients with Brugada syndrome [1]. I would like to call attention to my previous publications on this subject.…”
mentioning
confidence: 98%